Assessment of Adult ADHD With College Students. Issue 14 (December 2019) - Drake, Morgan B.; Riccio, Cynthia A.; Hale, Nicole Svenkerud
Objective: When assessing adult ADHD, self-report measures are commonly used to guide clinical diagnosis. Self-report measures may be broadband covering a range of behaviors or narrowband and specific to symptoms associated with ADHD.Method: This study examined the results of broadband and narrowband measures for college students referred for evaluation of ADHD at a university clinic.Results: With consideration of diagnosis, which included additional information, the group of students who received a diagnosis of ADHD differed significantly from those who did not receive an ADHD diagnosis only on the symptom sets associated with ADHD for both the broadband and narrowband. At the same time, for the total sample, significant correlations emerged for ADHD symptoms with social stress, anxiety, and sense of inadequacy.Conclusion: This suggests the need for consideration of alternative or co-occurring factors influencing symptom presentation and functional impairment.